Inhibition of calpain9 attenuates peritoneal dialysis-related peritoneal fibrosis - Li, Fang; Wang, Yu; Tian, Jianwei; Zhou, Zhanmei; Yin, Wei; Qin, Xianhui; Wang, Huizhen; Zeng, Tao; Li, Aiqing; Jiang, Jianping (Frontiers in Pharmacology, 2022)
Aim: Peritoneal dialysis is a common renal replacement method for end-stage renal disease. Long-term peritoneal dialysis leads to peritoneal dialysis-related peritoneal fibrosis, which leads to a cessation of treatment. Calpain is a protein belonging to calcium-dependent endopeptidase family and plays an important role in extracellular matrix remodeling. Here, we evaluated the effect of calpain in peritoneal dialysis-related peritoneal fibrosis. Methods: We established two animal models of peritoneal fibrosis and inhibited the activity of Calpain, and then collected peritoneal tissue to evaluate the progress of fibrosis and the changes of Calpain and β-catenin. We obtained Rat peritoneal mesothelial cells and Human peritoneal mesothelial cell line and stimulated with TGF-β to produce extracellular matrix. Next we inhibited Calpain activity or reduced Calpain9 expression, and then assessed changes in extracellular matrix and β-catenin. Results: Inhibition of calpain activity attenuated chlorhexidine glucose and peritoneal dialysis-induced peritoneal thickening and β-catenin expression in mice. In addition, compared with the control group, when primary rat peritoneal mesothelial cells or human peritoneal mesothelial cells were treated with transforming growth factor beta, down-regulation of calpain activity inhibited the expression of Fibronectin and Collagen I, and increased the expression of E-cadherin. These changes could be adjusted after silencing calpain9. Finally, calpain9 deficiency was associated with down-regulation of Fibronectin and β-catenin in human peritoneal mesothelial cells. Conclusion: Our results suggest that calpain9 may be a key molecule in mediating peritoneal dialysis-related peritoneal fibrosis.